Evolutionary insight on localization of 18S, 28S rDNA genes on homologous chromosomes in Primates genomes - Mazzoleni, Sofia; Rovatsos, Michail; Schillaci, Odessa; Dumas, Francesca (Comparative cytogenetics, 2018)
We explored the topology of 18S and 28S rDNA units by fluorescence in situ hybridization (FISH) in the karyotypes of thirteen species representatives from major groups of Primates and Tupaia minor (Günther, 1876) (Scandentia), in order to expand our knowledge of Primate genome reshuffling and to identify the possible dispersion mechanisms of rDNA sequences. We documented that rDNA probe signals were identified on one to six pairs of chromosomes, both acrocentric and metacentric ones. In addition, we examined the potential homology of chromosomes bearing rDNA genes across different species and in a wide phylogenetic perspective, based on the DAPI-inverted pattern and their synteny to human. Our analysis revealed an extensive variability in the topology of the rDNA signals across studied species. In some cases, closely related species show signals on homologous chromosomes, thus representing synapomorphies, while in other cases, signal was detected on distinct chromosomes, leading to species specific patterns. These results led us to support the hypothesis that different mechanisms are responsible for the distribution of the ribosomal DNA cluster in Primates.
Keywords: tree shrew; Primates; synapomorphy; repetitive DNAs; Fluorescence in situ hybridization